An assessment of the Small-Scale Irrigation Management Turnover Program in Indonesia - Vermillion, Douglas L.; Samad, M.; Pusposutardjo, S.; Arif, S.S.; Rochdyanto, S. (International Water Management Institute, 2000)
Examines the extent to which the Government of Indonesia's aspirations were realized through turnover program adopted in 1987. The impacts of management turnover on irrigation management and irrigated agriculture in selected systems in West and Central Java are analyzed. This study is part of a comparative research program to examine the impacts of irrigation management transfer in several countries using a common methodology.